Rituximab combined with DexaBEAM followed by high dose therapy as salvage therapy in patients with relapsed or refractory B‐cell lymphoma: mature results of a phase II multicentre study. (28th December 2014) - Kirschey, Sebastian; Flohr, Thomas; Wolf, Hans H.; Frickhofen, Norbert; Gramatzki, Martin; Link, Hartmut; Basara, Nadezda; Peter, Norma; Meyer, Ralf G.; Schmitz, Norbert; Weidmann, Eckhart; Banat, Andre; et al.
Summary Salvage therapy followed by high‐dose therapy (HDT) remains a mainstay for patients with relapsed lymphoma, however no optimal regimen has been defined. Here we report on the results of R‐DexaBEAM (rituximab, dexamethasone, carmustine, etoposide, cytarabine, melphalan) followed by HDT. Patients aged 18–65 years, Eastern Cooperative Oncology Group performance score 0–2, with relapsed/refractory B‐cell non‐Hodgkin lymphoma (NHL) were eligible. R‐Dexa‐BEAM was given for two cycles followed by stem cell mobilization and HDT. Primary endpoint of the trial was progression‐free‐survival (PFS). One hundred and three patients were included: aggressive NHL (aNHL): diffuse large B‐cell lymphoma 55, mantle cell lymphoma 7, follicular lymphoma (FL) grade 3: 5, indolent Lymphoma (iNHL): FL grade 1–2: 29, marginal zone lymphoma 6, Immunocytoma 1. The overall response rate after salvage therapy was 62% for aNHL and 78% for iNHL patients. 66% of patients with aNHL and 86% with iNHL underwent HDT. Treatment‐related mortality for HDT was 1·3%. For aNHL patients, the median PFS was 0·83 years with 44% alive at the median follow‐up of 7·3 years. Corresponding figures for iNHL were: median PFS 3·7 years and 72% alive after 8 years. The combination of rituximab with DexaBEAM followed by HDT resulted in high response rates and sustained remissions in responders. R‐DexaBEAM followed by HDT can be considered a valid salvage option for NHL.